2014
DOI: 10.4209/aaqr.2013.06.0212
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Facilitates the Germination of Plant Seeds

Abstract: We proposed a new approach to enhance the germination of plant seeds via the electrospray of nanoparticles (NPs). A single-capillary electrospray system with a particle deposition stage (where seeds are placed) was set up for this investigation. For demonstration, lettuce (Lactuca sativa) seeds were bombarded by TiO 2 NPs via the electrospray for 2-4 minutes in order to promote their germination. Based on our study, the enhancement in germination was significant in cases with aged seeds or seeds placed in an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…4,18 For instance, nano forms of NiO, CuO, TiO 2 , Co 3 O 4 , and Fe 2 O 3 have shown variable inhibitory effects on seed germination in radish, cucumber, and lettuce, which, however, differed with crop genotypes and seed size and followed the order: lettuce > cucumber > radish. 19 In a similar study, López-Moreno et al reported a substantial reduction in the germination of tomato (30%), cucumber (20%), and maize (30%) when exposed to cerium dioxide (CeO 2 ) NPs at 2000 mg l À1 while germination of alfalfa plant remained unaffected. 20 In contrast, the application of SiO 2 NPs even at 8 g l À1 dose rate did improve seed germination, seed vigor index, and the average germination time of tomato.…”
Section: Alfalfa (M Sativa)mentioning
confidence: 87%
“…4,18 For instance, nano forms of NiO, CuO, TiO 2 , Co 3 O 4 , and Fe 2 O 3 have shown variable inhibitory effects on seed germination in radish, cucumber, and lettuce, which, however, differed with crop genotypes and seed size and followed the order: lettuce > cucumber > radish. 19 In a similar study, López-Moreno et al reported a substantial reduction in the germination of tomato (30%), cucumber (20%), and maize (30%) when exposed to cerium dioxide (CeO 2 ) NPs at 2000 mg l À1 while germination of alfalfa plant remained unaffected. 20 In contrast, the application of SiO 2 NPs even at 8 g l À1 dose rate did improve seed germination, seed vigor index, and the average germination time of tomato.…”
Section: Alfalfa (M Sativa)mentioning
confidence: 87%
“…However, few studies have been carried out to test the positive and negative influence of TiO 2 -NPs on plants. Wu et al (2014) reported a positive effect of TiO 2 -NP on seed germination, when bombarded lettuce seeds via the electrospray technique, even at low pH or using aged seeds, and these positive effects of TiO 2 -NPs were found to operate in a time-dependent manner in Prunus mahaleb (Goodarzi et al, 2017) and wheat plant cv. Parsi (Mahmoodzadeh and Aghili, 2018).…”
Section: Titanium Dioxide Nanoparticles (Tio 2 -Nps)mentioning
confidence: 99%
“…Similarly, Au-NPs produced through green synthesis from the Terminalia arjuna fruit extract also enhanced seed germination of flame lily (G. superba), an endangered medicinal plant (Gopinath et al, 2014). A novel approach of NPs application was investigated to find the possible effects on the seed germination by applying the electrospray technique to bombard Au-NPs on lettuce and grass seeds either under stress conditions (e.g., low pH medium) or for aged seeds (Wu et al, 2014). Zaka et al (2016) documented no inhibitory effects of Au-NPs when they investigated Au-NPs, Cu-NPs, and Ag-NPs against seed germination frequency of E. sativa, and likewise, Au-NPs did not affect seed germination when tested against barley seeds (Feichtmeier et al, 2015).…”
Section: Gold Nanoparticles (Au-nps)mentioning
confidence: 99%
“…However, Karaboon et al (2005) found that scarification the Cassia fistula seeds with sulfuric acid for 15-20 min represented the best treatment for enhancing germination, but mechanical scarification (by piercing the seeds at the part of cotyledon) showed slightly lower effects (statistically significant). Recently Wu et al (2014) reported that TiO 2 nanoparticles effectively electrospray (using single-capillary electrospray) dispersed nanoparticles for breaking the seed coat to enhance seed germination percentage of lettuce seeds. However, this method may be not simple to use due to the requirement of a technical apparatus and absence of adequate information on its efficiency in seeds with hard coat dormancy.…”
Section: Discussionmentioning
confidence: 99%